Три медведя: [русские народные сказки] : [0+] / худ. В. Л. Вахтин - Вахтин В. Л. (Читаю сказки, 2012)
Экземпляры: ф.5 (20140917) / Инвентарный номер: 46020 / Цена: 65.00 / Сис.шифр: Д / Авт.знак: Т 67 / ГРНТИ: 17.71 / ББК: 82.3(2)